Handbook of polymers for electronics - Wypych, George (ChemTec Publishing, 2021)
"Polymers used in electronics and electrical engineering are essential for the development of high-tech products, including applications in space, aviation, health, automotive, communication, energy harvesting, energy storage, light-emitting and sensing, flexible electronics, robotic systems, analytical sensors, consumer products, and many others."--